Examining the Relationship between a Verbal Incidental Learning Measure from the WAIS-IV and Neuroimaging Biomarkers for Alzheimer's Pathology. Issue 3 (2nd April 2020) - Hammers, Dustin B.; Kucera, Amanda; Spencer, Robert J.; Abildskov, Tracy J.; Archibald, Zane G.; Hoffman, John M.; Wilde, Elizabeth A.
ABSTRACT: Convergent validation of a verbal incidental learning (IL) task from the WAIS-IV using neuroimaging biomarkers is warranted to understand its sensitivity to Alzheimer's disease (AD) pathology. Fifty-five memory clinic patients aged 59 to 87 years received neuropsychological assessment, and measures of IL and quantitative brain imaging. Worse IL-Total Score and IL-Similarities performances were significantly associated with smaller hemispheric hippocampal volumes. IL measures were not significantly correlated with cerebral β-amyloid burden, though a trend was present and effect sizes were mild. These hippocampal volume results suggest that this IL task may be sensitive to AD pathology along the AD continuum.